Pengaruh Kapitalisasi Pasar, Profitabilitas dan Leverage terhadap Nilai Perusahaan : (Emiten Properti dan Real Estate di Bursa Efek Indonesia Periode 2020-2023) - Aulia Pramesti; Wastam Wahyu Hidayat; Gilbert Rely (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to test and analyze market capitalization, profitability and leverage on firm value (property and real estate issuers on the Indonesian stock exchange for the period 2020-2023). The sampling technique used was purposive sampling method and obtained 15 issuers for 4 years, a sample of 60 issuers. The results showed that partially market capitalization has a positive and significant effect on firm value and profitability and leverage variables have no significant effect on firm value.